Parents of Children with Disabilities: Strengths and Frailty of Human Faith Journeys - Ductrám, Peter Joseph (Journal of disability & religion, 2025)
Although studies have been conducted regarding the faith journeys of people with disabilities, little is known of those nurturing and accompanying them, their parents. The faith journeys of parents of children with disabilities are a critical yet underattended source of theological insight. In this qualitative research study, we interview and study the perspective of seven married parents of children with disabilities who actively participate in ministry at their local faith communities or a national arena. While these criteria limit the number of parents caring for children with disability, they gave us greater insight into the challenges and graces received throughout their faith journeys, the role of their immediate family, their faith communities, and the universal Church. Five emerging themes were identified reflecting the rich yet complex strengths and frailty of their faith journeys. This study intends to amplify the stories of parents of children with disabilities becoming key conversation partners. Their hope-in-tension narratives inform and challenge the understanding of Christian anthropology, the centrality of faith, and the vocation of marriage, and in turn lead to concrete pastoral recommendations in three critical dimensions: ecclesiological, catechetical, and ministerial.